The Emergence of a State's Sovereignty in a Philosophical Dimension - Yunus, Nur Rohim (BULETIN ADALAH, 2019)
The essay entitled The Emergence of State Sovereignty in a Philosophical Dimension examines in depth the concept of sovereignty in a philosophical context, starting from the basic understanding to its role in the formation of the state. This essay discusses how sovereignty becomes a fundamental principle that affirms the highest authority of a state in regulating its territory and people without external intervention. By examining classical to modern views, such as the social contract theory of Hobbes and Rousseau and the concept of absolute power according to Bodin, this essay explains that sovereignty can only exist through the existence of the state as a legitimate political entity. In addition, this essay outlines the reciprocal relationship between the state and sovereignty, and highlights the evolutionary view that encourages the adaptation of sovereignty to social developments. In closing, this essay emphasizes that sovereignty reflects the superiority of the state in determining its own destiny, while also being the main foundation in maintaining stability and order in the international system.